TV advertising and children’s consumer culture - Reda Ponelienė; Sigitas Balčiūnas (Problemy Wczesnej Edukacji)
The paper presents the results of the research on consumer experience of 6–7 year old children investigated from the child’s perspective. The authors employed the method of interview with the child about TV advertisements, using stimulus material. The authors state that children recognize TV advertisements shown for them, make a distinction between advertisements and other television programmes, and have a certain knowledge about them. The study disclosed that the child’s approach to advertising depends on adults’ behaviour. It also revealed rudiments of critical assessment of advertising, which are mainly determined by negative experience of the child itself using the advertised item. According to the authors, in order to achieve the child’s critical attitude towards consumption and advertising, the adult who is together with the child must have similar features and values.